Treatment Combining Focused Ultrasound with Gastrodin Alleviates Memory Deficit and Neuropathology in an Alzheimer’s Disease-Like Experimental Mouse Model - Kaixuan Luo; Yuhong Wang; Wen-Shiang Chen; Xiangjun Feng; Yehui Liao; Shaochun Chen; Yao Liu; Chengde Liao; Moxian Chen; Lijuan Ao (Neural Plasticity)
Alzheimer’s disease (AD) is the most common type of dementia but lacks effective treatment at present. Gastrodin (GAS) is a phenolic glycoside extracted from the traditional Chinese herb—Gastrodia elata—and has been reported as a potential therapeutic agent for AD. However, its efficiency is reduced for AD patients due to its limited BBB permeability. Studies have demonstrated the feasibility of opening the blood-brain barrier (BBB) via focused ultrasound (FUS) to overcome the obstacles preventing medicines from blood flow into the brain tissue. We explored the therapeutic potential of FUS-mediated BBB opening combined with GAS in an AD-like mouse model induced by unilateral intracerebroventricular (ICV) injection of Aβ1-42. Mice were divided into 5 groups: control, untreated, GAS, FUS and FUS+GAS. Combined treatment (FUS+GAS) rather than single intervention (GAS or FUS) alleviated memory deficit and neuropathology of AD-like mice. The time that mice spent in the novel arm was prolonged in the Y-maze test after 15-day intervention, and the waste-cleaning effect was remarkably increased. Contents of Aβ, tau, and P-tau in the observed (also the targeted) hippocampus were reduced. BDNF, synaptophysin (SYN), and PSD-95 were upregulated in the combined group. Overall, our results demonstrate that FUS-mediated BBB opening combined with GAS injection exerts the potential to alleviate memory deficit and neuropathology in the AD-like experimental mouse model, which may be a novel strategy for AD treatment.